A core-shell structured CoMoO4⋅nH2O@Co1-xFexOOH nanocatalyst for electrochemical evolution of oxygen. (10th June 2020) - Wang, Jiajun; Yin, Hui; Chen, Zhengjun; Cao, Guoxuan; Xu, Ning; Wu, Hui; Wang, Ping
Abstract: Nickel-iron oxyhydroxide (Ni1-x Fex OOH) is well recognized as the best-performing oxygen evolution reaction (OER) catalyst in alkaline electrolytes, however its analogue cobalt-iron oxyhydroxide (Co1-x Fex OOH) is surprisingly less explored despite their structural similarity. Inspired by our recent study on high-performance HER catalyst using the nanostructured CoMoO4 ⋅nH2 O precursor, herein, we report a facile synthesis of Co1-x Fex OOH catalyst derived from the same precursor and its excellent electrocatalytic properties towards the OER in alkaline electrolytes. A core-shell structured nanocatalyst consisting of disordered Co1-x Fex OOH layer over the surface of crystalline CoMoO4 ⋅nH2 O nanosheets was synthesized using a simple hydrothermal method followed by anodic electrooxidation. Thus-prepared catalyst exhibited extraordinarily high and stable activity towards the OER in alkaline electrolyte, which outperformed most Co-based OER catalysts. Combined with the HER catalyst derived from the same CoMoO4 ⋅nH2 O precursor as the cathode, we further developed and tested a simple water-splitting cell, which significantly surpasses the benchmarking IrO2 –Pt/C couple (1.63 V) and requires a voltage of only 1.517 V to afford 10 mA cm −2 in 1.0 M KOH solution. Density functional theory calculations were conducted to gain insight into the Fe-doping induced improvement of OER activity. Graphical abstract: Image 1 Highlights: A core-shell structured CoMoO4 ⋅nH2 O@Co1-x Fex OOH nanocatalyst is facilely synthesized. The catalyst shows high and stable activity towards the OER in alkaline electrolyte. DFT calculations are conducted to understand the effect of Fe-doping on OER activity.